A retrospective analysis of EBV‐DNA status with the prognosis of lymphoma. Issue 20 (6th September 2022) - Qiu, Lihua; Si, Junqi; Kang, Junnan; Chen, Zehui; Nuermaimaiti, Rexidan; Qian, Zhengzi; Li, Lanfang; Zhou, Shiyong; You, Mingjian James; Zhang, Huilai; Tian, Chen
Abstract: Epstein–Barr virus (EBV) infection is proved to be associated with clinicopathology of lymphoma. However, little is known about the relationship between EBV‐DNA status after treatment and prognosis. In this study, real‐time polymerase chain reaction (PCR) was used for quantitative detection of EBV‐DNA load in peripheral blood of all 26, 527 patients with lymphoma, and the clinical characteristics and prognosis of 202 patients were retrospectively analysed, including 100 patients with positive EBV‐DNA and 102 randomly selected patients with negative EBV‐DNA. We found that the average rate of EBV‐DNA positivity in lymphomas was 0.376%, and EBV‐DNA‐positive patients presented higher risk with elevated lactate dehydrogenase (LDH) and β2‐MG level, B symptoms, secondary hemophagocytic syndrome and lower objective response rate compared to EBV‐DNA‐negative patients. Multivariate analysis revealed EBV‐DNA‐positive patients had inferior progression‐free survival (PFS) and overall survival (OS) and EBV‐DNA level before treatment was related to PFS but not OS of T/NK cell lymphoma. In T/NK cell lymphoma, EBV‐DNA converting negative after treatment was correlated with better PFS but not OS, and second‐line therapy could induce more EBV‐DNA‐negative conversion compared to CHOP‐based therapy. In all, EBV‐DNA positivity before treatment can be a biomarker representing the tumour burden and an independent prognostic factor. EBV‐DNA‐negative conversion after treatment is a good prognostic factor for T/NK cell lymphomas.